Efficiency and Fairness in Distributed Wireless Networks Through Self-interference Cancellation and Scheduling - Radunovic, Bozidar; Gunawardena, Dinan; Proutiere, Alexandre; Singh, Nikhil; Key, Peter; Balan, Vlad (2009)
Handling interference is one of the major challenges in the design of multi-user distributed wireless systems. In current systems, interference is managed through carrier sensing mechanisms such as CSMA/CA and through MAC algorithms based on random back-off. However, the asymmetry in channel sensing inevitably causes degraded throughput and fairness issues, such as those caused by hidden terminal problems. We propose ContraFlow, a solution based on self-interference cancellation and innovative scheduling mechanisms that increases spatial reuse, eliminates hidden terminals, and rectifies decentralized coordination inefficiencies among nodes, thereby improving fairness. Self-interference cancellation is a technique allowing a node to cancel its own transmitted signal and hence to successfully receive data while transmitting on the same channel. We demonstrate the feasibility of such techniques in a low power WPAN setting, using Lyrtech software-defined radios. Self-interference cancellation repairs carrier sensing, making it possible to successfully eliminate hidden terminal problems, even when using current multi-user MAC protocols; but it also provides the opportunity to design new distributed MAC scheduling algorithms that increase the spatial reuse and solve most of the fairness problems associated with current algorithms. We use simulations to illustrate the performance gains achieved when ContraFlow is used and we obtain both a throughput increase over current systems, as well as a significant improvement in fairness.